Evaluation of the presence of dental pain in Guarani and Tupiniquim indigenouspopulations aldeada do Espírito Santo - Berger Velten, Deise; Geraldo Mill, José; Monteiro de Barros Miotto, Maria Helena (Guará Journal, 2023)
Objective: to evaluate the prevalence of toothache and its association with sociodemographic characteristics, education, use of dental services and need for dental prostheses in an indigenous population living in the municipality of Aracruz - Espírito Santo. Methodology: Cross-sectional research in which 1084 Guarani and Tupiniquim indigenous people living in the municipality of Aracruz were evaluated regarding the presence of dental pain, sociodemographic characteristics, use of dental services and need for dental prosthesis. Fisher’sexact test (p
Keywords: Health of indigenous populations; Toothache; Dental care